Medications Adherence and Associated Factors among Patients with Type 2 Diabetes Mellitus in the Gaza Strip, Palestine - Elsous, Aymen; Radwan, Mahmoud; Al-Sharif, Hasnaa; Abu Mustafa, Ayman (Frontiers in Endocrinology, 2017)
Aim: To evaluate adherence to anti-diabetes medications among type 2 DM seeking medical care in Gaza Strip, Palestine. Methods: A cross-sectional study was conducted among 369 primary care patients with type 2 DM from October to December 2016. Adherence to medications was measured using the Morisky Medication Adherence Scale (MMAS-4). Socio-demographic and clinical variables, provider patient relationship, health literacy and health belief were examined for each patient. Univariate, binary logistic regression and multiple linear regression were applied to determine independent factors influencing adherence to anti-diabetes medications using SPSS version 22. Results: Of all the respondents, 214 (58%), 146 (39.5%) and 9 (2.5%) had high (MMAS score = 0), medium (MMAS score = 1+2) and low (MMAS score ≥ 3) adherence to anti-diabetes medications respectively. Factors that were independently associated with adherence to anti-diabetes medications were: female gender (OR: 1.657, 95% CI: 1.065-2.578) and perception of disease’s severity (OR: 1.510, 95% CI: 0.410-5.560). Elderly (t = 1.345) and longer duration of DM (t = 0.899) were also predictors for adherence but showed no statistical significance (p > 0.05). Conclusion: The level of complete adherence to anti-diabetes medications was suboptimal. New strategies, that aim to improve patients’ adherence to their therapies, are necessary taking into considerations the influencing factors and the importance of having diabetes educators in the primary care centers.